Contribution of Ukrainian scientists in the government debt theory - Yulia Stakhiv (Cхід, 2013)
The theoretical analysis of recent scientific publications on national debt theories and methods of its administration was made in the given article. Also the basic concepts of debt, developed by foreign scientists were specified. The basic concepts of debt include classical and Keynesian. The first concept involves the negative influence of national debt on the economy, the second - followed by positive growth. National scientists not only developed the following theories, but also introduced novelty of these theories. It should be noted that the attitude of scientists to the national debt was changing along the changes of the economic system, development of the financial and economic relations inside the society. This article also shows the use of various theories in practice, common and different in basic theories of debt, as well as the doctrine of national and foreign scholars. The value of this paper is that the studies of Ukrainian scientists are significant not only for the national financial science, but also found practical application worldwide.